IZA Journal of Labor Economics - Cahuc, Pierre; Ayhan, Sinem H.; Hersch, Joni.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The IZA Journal of Labor Economics publishes scientific articles in all areas of labor economics. This refers to original high-quality theoretical and applied contributions on both microeconomic and macroeconomic labor-related topics. In particular, the IZA Journal of Labor Economics encourages submissions in subject areas that are closely linked to the various IZA Program Areas, ranging from education, family and environment to mobility, behavioral and personnel economics, and labor market institutions, among others. The IZA Journal of Labor Economics is part of IZA$1 (Bs mission of contributing to social and economic discourse, enabling political decision-making to be based on the best available scientific knowledge. We want to stimulate research to close knowledge gaps. Hence, the IZA Journal of Labor Economics particularly welcomes contributions that provide scientifically sound answers to open and relevant questions of modern labor economics.s
Keywords: Labor economics; Population; Labor Economics; Population Economics